Effect of Iota-Carrageenan and Its Hydrolysates on the Stability of Milk Ice Cream Mixes - Anna Kot; Ewa Jakubczyk; Magdalena Buniowska-Olejnik; Anna Kamińska-Dwórznicka (Polish Journal of Food and Nutrition Sciences)
The objective of this research was to determine the influence of iota-carrageenan and its acid and enzymatic hydrolysates on the physical properties of milk ice cream mixes. The main factors considered were the Turbiscan stability index, backscattering profile, particle size distribution and median diameter (D 50 ), the consistency index and the flow behavior index of ice cream mix before and after 24 h of maturation at 4°C. The microstructure of emulsion was also analysed based on confocal laser scanning microscopy (CLSM). The addition of iota-carrageenan resulted in lower stability of emulsion compared to emulsions with its acid and enzymatic hydrolysates. The sedimentation, coalescence and flocculation were observed based on the backscattering profile and CLSM images. The addition of stabilisers contributed to an increase in D50 of ice cream mix from 17.56 to 37.05–45.50 µm before maturation and from 34.73 to 46.73 µm after maturation. The iota-carrageenan after commercial lactase treatment improved the stability of milk ice cream mixes by increasing the consistency index to 0.104 and a flow behaviour index to 0.702. Finally, it may be concluded that the stabilisers used – iota-carrageenan and its hydrolysates – significantly influenced the physical properties of milk ice cream mixes and, hence, can be used as beneficial ingredients in the recipe of milk ice cream mixes.